Hydrogenated black TiO2 nanowires decorated with Ag nanoparticles as sensitive and reusable surface-enhanced Raman scattering substrates1. Issue 44 (16th May 2015) - Shan, Yufeng; Yang, Yong; Cao, Yanqin; Yin, Hao; Long, Nguyen Viet; Huang, Zhengren
<x xml:space="preserve">Abstract</x> Ag nanoparticle decorated hydrogenated TiO2 nanowires are fabricated as surface-enhanced Raman scattering substrates that are self-cleaning and reusable, and show high reproducibility, sensitivity, and stability.